Pengaruh PDB (Produk Domestik Bruto), Suku Bunga, dan Inflasi Terhadap Profitabilitas Bank Syariah Periode 2014-2017 - Muhammad Irsyad; Ahmad Mulyadi Kosim; Hilman Hakim (TAFAQQUH, 2018)
The purpose of this research is to analyze the influence GDP (gross domestic product), interest rate,and  Inflation toward ROA (return on asset). The method that writer applied is multiple regression linear.The data are secondary, based on finance report 4 years. The results show that are simultaneous influence of variable GDP (grossdomestic product), Interest Rate,and Inflation toward ROA (return on asset).The result also show there is a significant partially influence toward ROA (returnon asset), whereas Interest Rate has no partially Influence toward ROA (return on asset). The result adjusted R square show that the influence of GDP (gross domestic product), interest rate,and  Inflation toward ROA are 94,6%,  and the rest 5,4% was affected by othervariables and not included into this regression analysis.